Physical Activity as a Critical Component of First-Line Treatment for Elevated Blood Pressure or Cholesterol: Who, What, and How?: A Scientific Statement From the American Heart Association - Barone Gibbs, Bethany; Hivert, Marie-France; Jerome, Gerald J; Kraus, William E; Rosenkranz, Sara K; Schorr, Erica N; Spartano, Nicole L; Lobelo, Felipe (Hypertension (Dallas, Tex. 1979), 2021)
Current guidelines published by the American Heart Association and the American College of Cardiology broadly recommend lifestyle approaches to prevent and treat elevated blood pressure and cholesterol. For patients with mildly or moderately elevated blood pressure and blood cholesterol, lifestyle-only approaches are the first line of therapy. The purpose of this scientific statement is to: (1) highlight the mild-moderate-risk patient groups indicated for lifestyle-only treatment for elevated blood pressure or cholesterol; (2) describe recommendations, average effects, and additional considerations when prescribing lifestyle treatment with physical activity; and (3) provide guidance and resources for clinicians to assess, prescribe, counsel, and refer to support increased physical activity in their patients. An estimated 21% and 28% to 37% of US adults, respectively, have mild-moderate-risk blood pressure and cholesterol and should receive lifestyle-only as first-line treatment. Of the recommended lifestyle changes, increasing physical activity has extensive benefits, including improving both blood pressure and blood cholesterol, that are comparable, superior, or complementary to other healthy lifestyle changes. Physical activity assessment and prescription are an excellent lifestyle behavior treatment option for all patients, including for the large population of mild-moderate-risk patients with elevated blood pressure and blood cholesterol.